Policy recommendation to members of the Russian Federal Government: Strong tobacco control measures as a key to reducing mortality - Barr, Anna Louise; Hall, Teresa; Holland, Emilia; Rafeeg, Nazla; Chacon, Silvia Segovia; Taymor, Emilie; Walker, Inna; Zatoński, Mateusz (Journal of Health Inequalities, 2016)
Tobacco-related diseases are among the most significant contributors to Russia’s premature mortality burden. Smoking prevalence has been rising in Russia in the last decades, leading to worsening health and economic outcomes. This policy recommendation to members of the Russian Federal Government suggests that Russia carry out legislative and tobacco control measures including increasing the tax on tobacco products, better enforcement of smoke-free legislation, and the introduction of graphic warning on tobacco products, in order to tackle this public health.